2006
DOI: 10.1002/itdj.20044
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of health information systems in South Africa: The challenge of local sustainability

Abstract: The implementation and development of routine health information systems continue to provide a number of challenges for managers-the more so in developing countries where resources are scarce and human resource and technical skills limited. This article conceptualizes the interdependence between the local adaptation and appropriation of global standards, and the value that this adds to the global standard through improved quality of data. These processes reinforce one another in the creation of sustainable inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 11 publications
2
36
0
1
Order By: Relevance
“…As a result, studies have shown how many rural health workers pay lip service to the exercise of filling forms manually and inputting data into the HIS. Other scholars have argued that while part of the health reform agenda requires overall standardisation of indices for reporting, the actual implementation of standards at the local level often demands flexibility and adaptation according to the local situation (Jacucci et al, 2006;Sahay and Latifov, 2009). Some studies have brought evidence to show that in reality there is a high dependency of local health planners on soft data obtained from informal information sources outside the formal information system (Mutemwa, 2006;Miscione, 2007;Williamson and Kaasboll, 2009).…”
Section: Hismentioning
confidence: 98%
“…As a result, studies have shown how many rural health workers pay lip service to the exercise of filling forms manually and inputting data into the HIS. Other scholars have argued that while part of the health reform agenda requires overall standardisation of indices for reporting, the actual implementation of standards at the local level often demands flexibility and adaptation according to the local situation (Jacucci et al, 2006;Sahay and Latifov, 2009). Some studies have brought evidence to show that in reality there is a high dependency of local health planners on soft data obtained from informal information sources outside the formal information system (Mutemwa, 2006;Miscione, 2007;Williamson and Kaasboll, 2009).…”
Section: Hismentioning
confidence: 98%
“…Based on such findings, all users need to be able to effectively use the system in question, but the design should be a flexible one that evolves over time to meet the specific needs of the country in question-ideally, the HMIS should be simple, of high quality, responsive, scalable, adaptable, stable, and robust (Kimaro and Nhampossa, 2007). Furthermore, local networks should conform to national standards or templates in terms of data usage and input and should expand on existing frameworks where necessary (Jacucci, Shaw, and Braa, 2006).…”
Section: Sustainability and Data Usementioning
confidence: 99%
“…Yet Jacucci et al (2006) argued that there is a need for local adaptation and appropriation of global standards so as to have quality data. A locally appropriated standard usually meets user requirements hence reducing the risk of multiple standards.…”
Section: Challenges Of Standardizing Health Information Systems In Dementioning
confidence: 99%